Welfare - Barry, Norman P. (Minneapolis : University of Minnesota Press, 1999)
"This is the second edition of a well-established study of perhaps the most controversial and contested concept in the social sciences. The book traces the historical origins of welfare to eighteenth-century sources in moral and social philosophy and shows how, in the evolution of the concept, doctrines of welfare have been associated with a variety of social philosophies, including utilitarianism, rights, individualism and collectivism."--BOOK JACKET.
"The result is a well-rounded text for students of politics, sociology and social policy, and an essential reference for researchers as well as those with a wider interest in the welfare state."--BOOK JACKET.
1. The Idea of Welfare in Political Thought -- 2. Utilitarianism and the Origins of Welfare Philosophy -- 3. Anti-individualism: From the Minimal State to the Welfare State -- 4. Liberal Political Economy and Welfare -- 5. The Critique of Individualism and the Ethics of Welfare -- 6. Justice, Equality and Welfare -- 7. Welfare, the Welfare State and Politics -- 8. Welfare: A Postscript.
Includes bibliographical references (p. [147]-151) and index.
Keywords: Public welfare; Welfare state